Über den unlokalen Existenzsatz für eine eindimensionale quasilineare parabolische Gleichung - Siltschenko, J.; Sobolevskij, P. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Ю. Т. Сильченко, П. Е. Соболевский. О нелокальной теореме существования для одномерного квазилинейного параболического уравненияJ. Silčenka, P. Sobolevskis. Apie nelokalinę egzistencijos teoremą vienmatei kvazitiesinei parabolinei lygčiai